The role of demographic factors and entrepreneurial skills in developing small agricultural projects in Lattakia - زهرة احمد; حيان سليمان (Latakia University Journal -Biological Sciences Series, 2025)
The research aimed to identify the role of demographic factors (age, gender, educational qualifications, number of family members) in developing small agricultural projects in Lattakia Governorate, study the impact of entrepreneurial skills (initiative, creativity, business management) on the success of these projects, and develop a vision for the initiative makers. And supporting bodies to support small agricultural projects in the region. To achieve the research objectives, a stratified random sample of 100 small agricultural projects was selected. The necessary data was collected using a questionnaire that was distributed to the research sample. The descriptive analytical method was adopted in analyzing the answers of the sample members using frequencies, percentages, arithmetic averages, and Cronbach’s reliability test. Alpha, Spearman’s correlation coefficient, Likert scale. The results showed that owners of small projects possess various entrepreneurial skills, as the general average of the Likert scale reached 3.41, with a good relative importance of 68.14%. The most important of these skills are the ability to innovate and create, awareness and continuous knowledge of modern production methods and technologies. It was also shown that the project workers possess experience. High efficiency, appropriate prices and quality of the necessary local raw materials, use of modern machines and equipment, and provision of facilities for financing small entrepreneurial projects are among the most important factors for the success and development of the project, as the general average of the scale reached 3.64, with a generally agreeable trend and a high relative importance of 72.7%. The results of testing the research hypotheses showed at the level of significance (0.05) that there is no statistically significant relationship between the gender of the project owner and the level of development of the project, the presence of a moderate inverse relationship with statistical significance between the age of the project owner and the level of development of the project, and the presence of a strong direct relationship with statistical significance between (level education, number of family members) and the level of development of the project.